Perbandingan Perlindungan Hukum Terhadap Anak Korban Kekerasan Dalam Rumah Tangga di Negara Indonesia, India, dan Malaysia - Harsanty, Ika; Permana, Yana Sukma (Neolectura, 2025)
Protection of children's rights basically refers directly to laws, policies, efforts and activitiest hat guarantee the realization of child protection. First, in addition to the existence of groups of children who experience obstacles in their growth and development both mentally, physically, and socially; this is based on the assumption that this group is easily dependent. Domestic violence (KDRT) is a serious problem that not only affects the affected couple, but also children who witness or become victims. The formulation of the problem in this study is as follows: 1) How is the legal protection for children who are revictims of domestic violence in Indonesia? and 2) How does it compare to the legal protection for children who are victims of domestic violence in other countries? The results of the study indicate that legal protection for children who are victims of domestic violence in Indonesia is currently seen from good laws and regulations, international and national legal instruments.Among the international legal documents in the Convention on the Rights of theChild and national legal documents can be found in Law Number 35 of 2014 concerning Amendmentsto Law Number 23 of 2002 concerning Child Protection and Law Number 23 of 2004 concerning Elimination of Children's Rights.domestic violence.